Karakteristik Perkembangan Tafsir al-Qur’an pada Abad IX (Analisis Historis Metodologis) - Andi Miswar (Universitas Islam Negeri Alauddin Makassar, 2018)
In the development of quranic interpretation, the IX century is known as the mutaakhhirin period. In this era interpretation shows fundamental change, for example the change from the form of bi al-ma’tsur (riwayah) exagesis to the form of dirayah (al-ra’yu) exegesis, as it is practiced in jalalayn exagesis by jalaluddin al-mahally and jalaluddin al-sayuti that it is using ijmali or global method, and placing exegesis within it is global or general context. The exagesis book was published in that century is the interpretation of tafsir tanwir al-miqbas min tafsir Ibnu Abbas exegesis by al-fairuzabādi applies ijmali method such as tafsir bi al-ma’tsur and tafsir al-Dūr al-mansūr fi tafsir al-ma’tsūr by jalaluddin al-sayuti, which applying ijmali and muqāran, in the form of tafsir bi al-ma’tsur, the exagesis is classified as general exegesis. The tendency of exegesis mostly impluenced by their personal understanding, school of thought, and qualification of their knowledge.Dalam Perkembangan tafsir al-Qur’an, abad IX dikenal dengan periode mutaakhhirin. Di era ini kegiatan penafsiran mengalami perkembangan yang cukup signifikan, misalnya dari bentuk tafsir bi al-ma’tsur (riwayah) ke bentuk tafsir dirayah (al-ra’yu) seperti yang terdapat dalam Tafsīr Jalalayn Oleh Jalaluddin al-Mahally dan Jalaluddin al-Syayuti yang menggunakan metode ijmāli atau global, serta memberikan gambaran penafsiran yang bercorak umum. Kemudian beberpa tafsir yang lahir pada masa tersebut, diantaranya, Tafsīr Tanwīr al-miqbās min tafsīr Ibnu Abbās oleh al-fairuzabādi menggunakan metode ijmāli dengan kategori bentuk tafsir bi al-Ma’tsūr, Dan Tafsīr al-Dūr al-Mantsūr fi tafsir al-ma’tsūr oleh Jalaluddin al-Sayūti disamping menggunakan metode muqāran juga ijmali, dengan bentuk tafsir bi al-ma’tsūr tafsir ini dikategorikan pula bercorak umum. Kecendrungan Mufassir dalam melakukan penafsiran kebanyakan dipengaruhi oleh pemahaman pribadi, mazhab, dan kwalifikasi keilmuan mereka.